2008
DOI: 10.1093/jpepsy/jsn115
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Internet-based Self-Management Interventions for Youth with Health Conditions

Abstract: There are the beginnings of an evidence base that self-management interventions delivered via the internet improve selected outcomes in certain childhood illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
217
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(231 citation statements)
references
References 33 publications
8
217
0
2
Order By: Relevance
“…Conflicting evidence regarding HRQL outcomes may have resulted from limited post-treatment follow-up (less than six months) and using nonspecific disease measures. The article concluded there was preliminary evidence that self-management interventions delivered via the Internet improved selected outcomes in certain chronic childhood illnesses (87).…”
Section: Innovative Approaches To Disease Self-management In Jiamentioning
confidence: 99%
“…Conflicting evidence regarding HRQL outcomes may have resulted from limited post-treatment follow-up (less than six months) and using nonspecific disease measures. The article concluded there was preliminary evidence that self-management interventions delivered via the Internet improved selected outcomes in certain chronic childhood illnesses (87).…”
Section: Innovative Approaches To Disease Self-management In Jiamentioning
confidence: 99%
“…In contrast, there have been randomised clinical trials in patients with specific diseases like asthma, depression, or diabetes. [30][31][32] The primary outcome of these trials was most often quality of life or clinical improvement. In some of these, hospitalisations and emergency department visits were studied but with inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…In some of these, hospitalisations and emergency department visits were studied but with inconsistent results. 30 Some randomised clinical trials aimed to assess the effectiveness of information leaflets on minor symptoms in children. A recent trial among children who already consulted primary care showed that an interactive booklet about childhood respiratory tract infections led to a reduction in antibiotic prescribing and reconsultations.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a DCD online module was developed and posted on a childhood disability research centre website; preliminary results highlighted improvement in self-perceived knowledge and skills but no information was available with regards to change in behaviours 20 . In childhood disability in general, a systematic review of internet-based self-management interventions for youth with chronic health conditions found conflicting evidence regarding the interventions' ability to improve disease-specific knowledge and quality of life 21 . Authors of this review concluded that we are just beginning to understand how internet-based resources could improve outcomes for children with disabilities.…”
mentioning
confidence: 99%
“…A few other studies of the use of web-based information with other chronic conditions of childhood were found in a systematic review 21 . Results indicated most interventions involved the provision of direct services through the internet (e.g., monitoring) and evaluated disease-specific outcomes related specifically to the child's condition (e.g., pain).…”
mentioning
confidence: 99%